2023
DOI: 10.3390/ijms241310837
|View full text |Cite
|
Sign up to set email alerts
|

Lung Surfactant Protein B Peptide Mimics Interact with the Human ACE2 Receptor

Abstract: Lung surfactant is a complex mixture of phospholipids and surfactant proteins that is produced in alveolar type 2 cells. It prevents lung collapse by reducing surface tension and is involved in innate immunity. Exogenous animal-derived and, more recently, synthetic lung surfactant has shown clinical efficacy in surfactant-deficient premature infants and in critically ill patients with acute respiratory distress syndrome (ARDS), such as those with severe COVID-19 disease. COVID-19 pneumonia is initiated by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…This implies that these synthetic peptides may function as competitive inhibitors, potentially obstructing the virus from attaching to the ACE2 receptor, thus either preventing infection or mitigating its severity. 48 …”
Section: Respiratory Surfactantsmentioning
confidence: 99%
“…This implies that these synthetic peptides may function as competitive inhibitors, potentially obstructing the virus from attaching to the ACE2 receptor, thus either preventing infection or mitigating its severity. 48 …”
Section: Respiratory Surfactantsmentioning
confidence: 99%
“…672,673 It is notable that the SP-B-C allele is associated with an increased incidence of RDS and an elevated severity of ARDS. 676−678 679 Patients bearing this pathogen demonstrate higher titers of anti-SP-B and anti-SP-C antibodies. Similar to SP-B, whereas SP-C has been mainly examined for its ability to aid formation of a surface film, recent studies by a number of investigators have demonstrated altered innate immunity in mice either lacking or with mutant forms of SP-C. For example, SFPC −/− mice show enhance susceptibility to a number of pathogens, including P. aeruginosa, and to respiratory syncytial virus.…”
Section: 541mentioning
confidence: 99%
“…Recent studies utilizing surface plasmon resonance indicate SP-B may interact directly with the angiotensin-converting enzyme 2 receptor, thereby providing steric hindrance toward infection by COVID-19 virus . Patients bearing this pathogen demonstrate higher titers of anti-SP-B and anti-SP-C antibodies.…”
Section: What Do Physiological and Pathophysiological Studies Teach U...mentioning
confidence: 99%